Muscle MRI findings in facioscapulohumeral muscular dystrophy - Gerevini, Simonetta; Scarlato, Marina; Maggi, Lorenzo; Cava, Mariangela; Caliendo, Giandomenico; Pasanisi, Barbara; Falini, Andrea; Previtali, Stefano Carlo; Morandi, Lucia (European radiology, 2016)
Objectives Facioscapulohumeral muscular dystrophy (FSHD) is characterized by extremely variable degrees of facial, scapular and lower limb muscle involvement. Clinical and genetic determination can be difficult, as molecular analysis is not always definitive, and other similar muscle disorders may have overlapping clinical manifestations. Methods and Materials Whole-body muscle MRI examination for fat infiltration, atrophy and oedema was performed to identify specific patterns of muscle involvement in FSHD patients (30 subjects), and compared to a group of control patients (23) affected by other myopathies (NFSHD). Results In FSHD patients, we detected a specific pattern of muscle fatty replacement and atrophy, particularly in upper girdle muscles. The most frequently affected muscles, including paucisymptomatic and severely affected FSHD patients, were trapezius, teres major and serratus anterior. Moreover, asymmetric muscle involvement was significantly higher in FSHD as compared to NFSHD patients. Conclusions In conclusion, muscle MRI is very sensitive for identifying a specific pattern of involvement in FSHD patients and in detecting selective muscle involvement of non-clinically testable muscles. Muscle MRI constitutes a reliable tool for differentiating FSHD from other muscular dystrophies to direct diagnostic molecular analysis, as well as to investigate FSHD natural history and follow-up of the disease. Key Points • Muscle MRI identifies a specific pattern of muscle involvement in FSHD patients. • Muscle MRI may predict FSHD in asymptomatic and severely affected patients. • Muscle MRI of upper girdle better predicts FSHD. • Muscle MRI may differentiate FSHD from other forms of muscular dystrophy. • Muscle MRI may show the involvement of non - clinical testable muscles.